PENGEMBANGAN PERANGKAT LUNAK PENGENDALI LENGAN ROBOT PADA APLIKASI LAS TITIK - Lubis, Imran (Jurnal TIMES, 2015)
Industrial automation robotics is essential in improving the efficiency and effectiveness of the overall productivity according to science writer elaborated that in the field of robotics has several branches, at least there are 3 branches of disciplines in the design of a robotic system which is the science of electricity (electronics, mechanics and programming techniques). In this moment I had the opportunity to elevate the field of programming in creating a robotic system with a particular function. The author focuses on the field of programming the robot to be designed. Topics raised design of a robot is a robot that iron welding spot welding robots. Because this discussion is only limited to the design of a prototype simulation spot welding robots, robots who built a miniature robot with props spot welding using materials or stationery ink and not the actual use of welding tools. Realization of welding robot design is a robotic arm with four degrees of freedom of movement (4 DOF) driven by 4 DC motors and stepper motors as a writer programmers to design programs to control robots built there are 2 programs which programs and program motor control transmitter or the remote control signal sender. The program is designed with Assembly language after compilation downloaded into the controller IC that is remote and motor control.